Response evaluation after neoadjuvant therapy: evaluation of chemotherapy response score and serological and/or radiological assessment of response in ovarian cancer patients - Ramspott, Jan Philipp; Baert, Thaïs; MacKintosh, Michelle Louise; Traut, Alexander; Ataseven, Beyhan; Bommert, Mareike; Heitz, Florian; Plett, Helmut; Schneider, Stephanie; Waltering, Kai-Uwe; Heikaus, Sebastian; Harter, Philipp; et al. (Archives of Gynecology and Obstetrics, 2021)
Purpose The chemotherapy response score (CRS) is a histopathological tool to evaluate response to neoadjuvant chemotherapy (NACT) in high-grade serous ovarian cancer (OC). We critically evaluated the clinical value of CRS and compared its predictive power to standard serological (CA125) and radiological response. Methods A retrospective analysis of 277 OC patients, who received primary chemotherapy, was performed. CRS, serological, and radiological findings were correlated with progression-free (PFS) and overall survival (OS). Results CRS could be determined in 172 of 277 patients (62.1%). In patients with CRS3, a longer median PFS and OS was observed compared with CRS1/2 patients (31.2 vs. 18.9, P < 0.001; 55.0 vs. 36.1 months, P = 0.050). CA125 and radiological response evaluation were also predictive for PFS and OS. Patients with serological and radiological complete response showed longer PFS (23.0 vs. 14.4, P = 0.011; 21.4 vs. 9.6 months, P < 0.001) and OS (49.5 vs. 29.0, P = 0.003; 45.0 vs. 12.9 months, P < 0.001). Patients with pathological complete response (pCR) had the best median PFS (52.8 months), even compared with non-pCR CRS3 (27.8 months). In the total study cohort, serological, and radiological complete response was better at predicting PFS (hazard ratio 2.23 and 2.77). Conclusion In this study, evaluation of response to chemotherapy by CRS was not superior to conventional methods (CA125 or radiology). Independent of the evaluation method, response to NACT was predictive of PFS and OS. We observed no added value for CRS as a prognostic marker. The clinical relevance of CRS should be discussed, as no therapeutic consequences result from CRS evaluation.